Survey of students of the degree course in obstetrics, on learning using case based learning (cbl) method in the area of professional teachings - Ricchi, A; Martelli, E; Molinazzi, M T; Vaccari, S; Messina, M P; Banchelli, F; Neri, I (Clinica terapeutica, 2018)
Case Based Learning (CBL) is a teaching methodology that, starting from a case associated with real life situations, is able to stimulate students to investigate, reflect and discuss to find the solution to the case. The aim of this study is to investigate the satisfaction and the educational impact on the students of the Obstetrics Degree Course on Learning Case Based Learning CBL (on real clinical cases). The observational study was carried out through the presentation of real clinical cases to a sample of 43 students of a degree course in Obstetrics and giving them questionnaires of evaluation regarding satisfaction and educational impact, using measurement scales which ranged from 1 (very bad) to 5 (excellent). The higher satisfaction was towards the tutor's exhibition capacity and the integration between participants, for 2nd and 3rd year students, respectively. Likewise, the highest educational impact was associated with the effectiveness of the tutor facilitator. Differences in the degree of satisfaction were observed between the two students cohorts, in particular regarding relevance of the topics, as satisfaction was higher in 2nd year students (p=0.021), and regarding work times, as satisfaction was higher in 3rd year students (p=0.042). No significant differences in the educational impact were observed between 2nd and 3rd year students. Studies were examined to compare the effectiveness of Case Based Learning (CBL) to the use of other teaching methodologies. The results of the study highlight that the knowledge and skills acquired by Case Based Learning were useful and applicable in the workplace.